Vaccination against the Intracellular Pathogens Leishmania major and L. amazonensis by Directing CD40 Ligand to Macrophages - Chen, Gang (American Society for Microbiology, 2001)
CD40 ligand (CD40L) is a potent inducer of interleukin-12 (IL-12) production from macrophages and dendritic cells. We show that combining CD40L with antigen derived from Leishmania is an effective way to preferentially induce type 1 immune responses to the antigen and to vaccinate mice against subsequent challenge with virulent organisms. Mice vaccinated in this way had smaller lesions, with more than 1,000-fold fewer parasites within them. To improve the efficiency of CD40L-induced immunopotentiation, we attempted to specifically direct CD40L to macrophages. We developed transfected cells expressing CD40L and a single Leishmania antigen, gp63. These cells bound efficiently to macrophages and induced robust IL-12 production. Vaccination with these cotransfected cells provided a significant degree of protection against challenge with virulent organisms. CD40L was also adsorbed to the surface of virulent Leishmania. These organisms induced only modest lesions in genetically susceptible mice, and the lesions had an average of 10(5)-fold fewer organisms within them relative to control mice. These studies suggest that CD40L could be exploited to improve vaccines against intracellular pathogens, especially those organisms that reside within cells expressing CD40 on their surface.